Calculation of vibrational energy of molecule using coupled cluster linear response theory in bosonic representation: convergence studies - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2008)
Vibrational excited state energies have been calculated using vibrational coupled cluster linear response theory (CCLRT). The method has been implemented on formaldehyde and water molecule. Convergence studies have been shown with varying the cluster operator from S(4) to S(6) as well as the excitation operator from four bosons to six bosons. A good agreement with full configuration interaction results has been observed with S(6) truncation at coupled-cluster method level and six bosonic excitations at CCLRT level. (C) 2008 American Institute of Physics.

Calculation of dipole transition matrix elements and expectation values by vibrational coupled cluster method - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Theory and Computation, 2010)
An effective operator approach based on the coupled cluster method is described and applied to calculate vibrational expectation values and absolute transition matrix elements. Coupled cluster linear response theory (CCLRT) is used to calculate excited states. The convergence pattern of these properties with the rank of the excitation operator is studied. The method is applied to a water molecule. Arponen-type double similarity transformation in extended coupled cluster (ECCM) framework is also used to generate an effective operator, and the convergence pattern of these properties is compared to the normal coupled cluster (NCCM) approach. It is found that the coupled cluster method provides an accurate description of these quantities for low lying vibrational excited states. The ECCM provides a significant improvement for the calculation of the transition matrix elements.

Vibrational multi-reference coupled cluster theory in bosonic representation - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Journal of Chemical Physics, 2012)
The vibrational multi-reference coupled cluster method is developed to calculate the vibrational excitation energies of polyatomic molecules. The method is implemented on ozone and formaldehyde molecules and the results are compared with full vibrational configuration interaction (FVCI) method. A good agreement is found between the vibrational multi-reference coupled cluster method and converged FVCI method for lower lying vibrational states. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4753422]

Study of molecular vibration by coupled cluster method: bosonic approach - Banik, Subrata; Pal, Sourav; Prasad, M. Durga (Proceedings of the International Conference of Computational Methods in Sciences and Engineering 2010 (ICCMSE-2010), 2015)
The vibrational coupled cluster method in bosonic representation is formulated to describe the molecular anharmonic vibrational spectra. The vibrational coupled cluster formalism is based on Watson Hamiltonian in normal coordinates. The vibrational excited states are described using coupled cluster linear response theory (CCLRT). The quality of the coupled cluster wave function is analyzed. Specifically, the mean displacement values of the normal coordinates <qi> and expectation values of the square of the normal coordinates <q(i)(2)> of different vibrational states are calculated. A good agreement between the converged full CI results and coupled cluster results is found for the lower lying vibrational states.</q(i)(2)></qi>
Keywords: CCLRT; Expectation values; Watson Hamiltonian